ANALISIS PENERJEMAHAN KALIMAT ELIPSIS VERBAL DALAM KOMIK NARUTO KARYA MASASHI KISHIMOTO KE DALAM BAHASA INDONESIA - Yesy Tri Cahyani; Amalina Iariva Putri Astria (STBA LIA - Jakarta, 2019)
Incomplete sentence (ellipsis verbal) are often to be the problem in translating from Japanese into Indonesian. The purpose of this research is to explain the techniques to translate incomplete sentence to achive equivalence found in Japanese comics Naruto volumes 29, 30, and 31, and analyze the translation of incomplete sentence contained in Naruto comic from Japanese to Indonesian. The method of this research is descriptive and qualitative methods. Data source are the Japanese comic title Naruto by Masashi Kishimoto as the source text, and the translation comic in Indonesia as the target text. Thirteen incomplete sentence data on source text were analyze using appropriate translation techniques to achieve equvalence in target text. The result showed that incomplete sentence had board meanings. In addition, incomplete sentence cannot be translate literally, without looking at the context. Context is an important reference so the messagges from source text can be conveyed.